Negotiating risk and uncertainty internal migration and rural villagers in Albay Province - Cooper, Hedda Ransan (Quezon City Ateneo de Manila University, 2015)
"This article examines the role of local discourses of risk and associated affective practices (embodied emotions) in decisions to migrate from rural to urban/peri-urban areas. Drawing on a study in a rural setting in Albay province, it argues that mobility decisions involve negotiation between public discourses about risk and a private self that considers one's capabilities and experiences. Although the risks associated with mobility are actively managed, these are imbued with uncertainty and are based on incalculate aspects of risk management such as hope and trust, especially among immediate social networks as practices of communal risk management have become increasingly undermined."
Keywords: Internal migration; Land reform; Risk; Agrarian change